Association between pre-hospital chest pain severity and myocardial injury in ST elevation myocardial infarction: A post-hoc analysis of the AVOID study - Himawan Fernando (Elsevier, 2021)
Background: We sought to determine if an association exists between prehospital chest pain severity and markers of myocardial injury. Methods and Results: Patients with confirmed ST elevation myocardial infarction (STEMI) treated by emergency medical services were included in this retrospective cohort analysis of the AVOID study. The primary endpoint was the association of pre-hospital initial chest pain severity, cardiac biomarkers and infarct size based on cardiac magnetic resonance imaging. Groups were categorized based on moderate to severe chest pain (numerical rating scale pain ≥ 5/10) or less than moderate severity to compare procedural and clinical outcomes. 414 patients were included in the analysis. There was a weak correlation between initial pre-hospital chest pain severity and peak creatine kinase (r = 0.16, p = 0.001) and peak cardiac troponin I (r = 0.14, p = 0.005). Both were no longer significant after adjusting for known confounders. There was no association between moderate to severe chest pain on arrival and major adverse cardiac events at 6 months (20% vs. 14%, p=0.12). There was a weak correlation between history of ischemic heart disease (r = 0.16, p = 0.001), percutaneous coronary intervention (r = 0.16, p = 0.001), left anterior descending artery (r = 0.12, p = 0.012) as the culprit vessel and a weak negative correlation between age (r = -0.14, p = 0.039) and chest pain. Conclusion: Only a weak association between pre-hospital chest pain severity and markers of myocardial injury was identified, supporting more judicious use of opioid analgesia with a focus on patient comfort.